2004
DOI: 10.1002/chem.200400036
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Aromatic Substitution by the Fluorofullerene C60F18

Abstract: The FeCl3-catalysed arylation of C60F18 gives tri-substituted compounds C60F15Ar3, where Ar=phenyl, 4-tolyl, 4-methoxyphenyl, 4-phenoxyphenyl, 4-chlorophenyl, 3,4-dichlorophenyl, 2-biphylenyl and 2-fluorenyl, together with some bis- and mono-substituted product. Bis-substitution was achieved with biphenylene and fluoranthene, and mono-substitution with biphenylene (2-position), pyrene (1-position), and naphthalene (1- and 2-positions); the tris-phenyl and tris-biphenylene derivatives are fluorescent. The 2-nap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
(33 reference statements)
2
16
0
Order By: Relevance
“…Lewis acid promoted reactions of C 60 F 18 with aromatics proceed through an S N 1 mechanism; therefore, aromatic residues directly replace three fluorine atoms thus yielding triumphenes that have the same addition pattern as the parent C 60 F 18 . [11] In contrast, trannulenes have a very different addition pattern because their formation from C 60 F 18 is operated by a rare S N 2'' mechanism in which the reacting nucleophiles (carbon anions À CXA C H T U N G T R E N N U N G (COOR) 2 ) become attached at the d positions with respect to carbon atoms bearing the leaving fluorine atoms. [12] Such remote addition gives rise to the formation of a fully aromatic 18-membered all-trans annulene (trannulene) ring on the equator of the molecule that separates the fluorinated crown lying on one fullerene hemisphere from three organic addends attached to the other hemisphere.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Lewis acid promoted reactions of C 60 F 18 with aromatics proceed through an S N 1 mechanism; therefore, aromatic residues directly replace three fluorine atoms thus yielding triumphenes that have the same addition pattern as the parent C 60 F 18 . [11] In contrast, trannulenes have a very different addition pattern because their formation from C 60 F 18 is operated by a rare S N 2'' mechanism in which the reacting nucleophiles (carbon anions À CXA C H T U N G T R E N N U N G (COOR) 2 ) become attached at the d positions with respect to carbon atoms bearing the leaving fluorine atoms. [12] Such remote addition gives rise to the formation of a fully aromatic 18-membered all-trans annulene (trannulene) ring on the equator of the molecule that separates the fluorinated crown lying on one fullerene hemisphere from three organic addends attached to the other hemisphere.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, compound 2 a (and presumably 2 b-e) is the first triumphene that comprises three aliphatic organic addends, which distinguishes it from previously synthesized triumphenes with three aryl groups. [11] Thus, thermal isomerization of trannulenes can be considered to be a convenient synthetic route for the preparation of novel triumphenes with aliphatic substituents that cannot be obtained directly from fluorofullerene C 60 F 18 .…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Up to now, the isomers of as-synthesized fullerenes [4,5] and corresponding fullerene derivatives, such as C 60 Cl 6 [6], C 60 Br 8 [7], C 60 Cl 30 [8], C 60 H 18 [9], C 60 F 18 [10,11], C 70 H 10 [12], C 70 Br 10 [13], and C 80 Cl 12 [14], satisfied the isolated pentagon rule (IPR). However, theoretical investigations have recently demonstrated that C 20 H 20 with completely fused pentagons was more energetically stable than IPRsatisfying C 60 H 60 [15].…”
Section: Introductionmentioning
confidence: 86%
“…However, recently experimental breakthrough on non-IPR fullerene derivatives demonstrates that the addend is not all necessary to be added to the pentagon-junction sites [23,24]. C 60 X 18 (X = H, F) [9,10,25,26] and C 70 X 10 (X = H, Cl, and Br) [11,12,27,28] have been successfully synthesized and wellcharacterized while reports on other number of derivatizations like C 60 X 12 [29], C 70 X 12 [30], etc. are relatively scarce.…”
Section: Introductionmentioning
confidence: 97%
“…Fluorofullerene C 60 F 18 is one of the most exotic fullerene derivatives [4] (Fig. 1) and the only fullerene fluoride that is a promising substrate for further derivatization by a nucleophilic substitution of three outlying fluorine atoms by organic addends [5]. However, C 60 F 18 is much less available than C 60 F 48 and C 60 F 36 since its preparation requires very specific fluorinating agents.…”
Section: Introductionmentioning
confidence: 99%